Congestion control for real-time communications: A comparison between NADA and GCC - Gaetano Carlucci; Luca De Cicco; Cesar Ilharco; Saverio Mascolo (24th Mediterranean Conference on Control and Automation (MED), 2016)
Congestion control for Web real-time communication (WebRTC) is a hot topic currently addressed at the IETF. Differently from congestion control for TCP, congestion control for WebRTC not only aims at containing packet losses, but also aims at minimizing queuing delays to provide interactivity. In this paper we describe two algorithms under discussion at IETF: Network Assisted Dynamic Adaptation (NADA) proposed by Cisco Systems and Google Congestion Control (GCC) proposed by Google. A performance comparison in a simulation environment is carried out. Results show that GCC exhibits slow convergence whereas NADA exhibits a remarkable oscillating behavior.
Keywords: Delays; Heuristic algorithms; Real-time systems; Receivers; Google; Loss measurement; Streaming media; low-delay communication; congestion control